Oligonol Inhibits Dextran Sulfate Sodium-Induced Colitis and Colonic Adenoma Formation in Mice - Yum, Hye-Won (Mary Ann Liebert, Inc., 2013)
Aims: To evaluate the effects of oligonol administration on experimentally induced colitis and colonic adenoma formation. Results: Oral administration of oligonol protected against mouse colitis induced by dextran sulfate sodium (DSS). Under the same experimental conditions, oligonol administration significantly inhibited the activation of nuclear factor-kappa B and signal transducer and activator of transcription (STAT) 3 and expression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and cyclin D1 in the mouse colon. Further, oligonol inhibited azoxymethane-initiated and DSS-promoted adenoma formation in the mouse colon. Oligonol administration also attenuated lipid peroxidation (malondialdehyde) and protein oxidation (4-hydroxy-2-nonenal), thereby preventing oxidative stress-induced apoptosis of colonic epithelial cells. In vitro studies demonstrated that oligonol treatment reduced lipopolysaccharide-induced expression of interleukin (IL)-1β, tumor necrosis factor α, il-6, cox-2, and inos in murine macrophage RAW 264.7 cells. In another study, oligonol upregulated the antioxidant gene expression in the intestinal epithelial CCD841CoN cells and in the mouse colon. Innovation: Oligonol, an innovative formulation of catechin-type oligomers derived from the lychee fruit extract, was tested in this study for the first time to evaluate its effects on experimentally induced colitis and colonic adenoma formation in mice. Conclusion: Oligonol is effective in protecting against DSS-induced mouse colitis and colon carcinogenesis, suggesting that this polyphenol formulation may have a potential for the amelioration of inflammatory bowel disease and related disorders. Antioxid. Redox Signal. 19, 102–114.